2023
DOI: 10.1001/jamanetworkopen.2023.10302
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Protein-Based SARS-CoV-2 Vaccine

Abstract: ImportanceThe protein-based SARS-CoV-2 vaccines FINLAY-FR-2 (Soberana 02) and FINLAY-FR-1A (Soberana Plus) showed good safety and immunogenicity in phase 1 and 2 trials, but the clinical efficacy of the vaccine remains unknown.ObjectiveTo evaluate the efficacy and safety of a 2-dose regimen of FINLAY-FR-2 (cohort 1) and a 3-dose regimen of FINLAY-FR-2 with FINLAY-FR-1A (cohort 2) in Iranian adults.Design, Setting, and ParticipantsA multicenter, randomized, double-blind, placebo-controlled, phase 3 trial was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
(75 reference statements)
0
11
1
Order By: Relevance
“…A study in Iran showed a different result from our study [15]. The seropositive rate was only 30% after 28 days of the booster dose administration [15]. Other studies have also shown that antibody levels after administration of a booster dose of the mRNA vaccine were higher than after administration of the protein subunit recombinant and viral vector vaccine [22][23][24].…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…A study in Iran showed a different result from our study [15]. The seropositive rate was only 30% after 28 days of the booster dose administration [15]. Other studies have also shown that antibody levels after administration of a booster dose of the mRNA vaccine were higher than after administration of the protein subunit recombinant and viral vector vaccine [22][23][24].…”
Section: Discussioncontrasting
confidence: 86%
“…A heterologous booster study was also conducted for Biological E's Corbevax, another vaccine with a similar platform to IndoVac ® Vaccine, which has been approved by the Indian Regulatory Authority as a heterologous booster for Covishield (ChAdOx1 vaccine) and Covaxin (inactivated vaccine) [21]. A study in Iran showed a different result from our study [15]. The seropositive rate was only 30% after 28 days of the booster dose administration [15].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The clinical trial phase III was conducted in the country in eight cities, and immunization by a three-dose regimen was significantly effective against hospitalization in the Delta variant era. PastoCovac was approved to be administrated to children above three years old, and at the same time, has been evaluated as an effective and safe booster vaccine for all primary vaccines in Iran [ 40 , 41 ] . In several studies carried out by PII (under review data), PastoCovac Plus immunogenicity was assessed among the individuals primarily immunized by two doses of Covaxin (BBV152), ChAdOx1-S, or BBIBP-CorV.…”
Section: Practical Methods For Management Of Covid-19 Chaosmentioning
confidence: 99%